2010
DOI: 10.1080/01434630903367215
|View full text |Cite
|
Sign up to set email alerts
|

The impact of incipient trilinguality on the socio-affective development of Jewish elementary school children in Israel

Abstract: For many decades now, applied linguistics studies have investigated the impact of second language acquisition on various aspects of the development of school children. Few studies, however, have focused on the simultaneous acquisition of two additional/second languages in the classroom. The present paper explores the impact of a spoken Arabic language programme in a Jewish elementary school in Israel on the children's socio-affective (attitudinal) development. The participants of the study comprised fourth-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(13 reference statements)
0
4
0
1
Order By: Relevance
“…Studies showed that participation in language courses improved learners’ attitudes toward the population that speaks that language (Bekerman, ; Guimond & Palmer, ). Similarly, Dubiner () found that Jewish elementary school children who studied spoken Arabic as a second language in school judged the Arabic language and the Arab community more favorably than children who did not.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies showed that participation in language courses improved learners’ attitudes toward the population that speaks that language (Bekerman, ; Guimond & Palmer, ). Similarly, Dubiner () found that Jewish elementary school children who studied spoken Arabic as a second language in school judged the Arabic language and the Arab community more favorably than children who did not.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Monologic exchange does not necessarily cause transfer (Mukhametzyanova, 2021) because feedback may be nonexistent or ineffective (Johnson, 2016). When learning, cognitive exchange may involve a teacher imparting information and a student appropriating knowledge (Dubiner, 2010), but it does not have to. Reciprocal exchanges could reverse or occur amongst peers, collaborators, or the self.…”
Section: Cognitive Exchange In Higher Degree Visual Art Educationmentioning
confidence: 99%
“…Eleven Phase 1 articles located cognitive exchange socially (Hernández-Sellés et al, 2020; Choi, 2009; Penman and Lai, 2003; Bosley et al 2006; Caspi and Blau, 2008; Guo et al, 2021; Duffett, 2015; Ding and Harskamp, 2006; Dubliner, 2010; Peacock and Cowan, 2017; Nicholson, 2007). Two connected cognitive exchange with art education, stating exchange occurs through leader and follower interaction (Nicholson, 2007) and collaboration (Hernández-Sellés et al, 2020).…”
Section: Literature Review Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Maurer-Hetto, 2009. Positiivsete väljundite poole pealt on leitud, et mitmekeelsus seostub divergentse mõtle misega (Konaka, 1997), metalingvistilise teadlikkuse ja täidesaatva kontrolliga (Bialystok & Barac, 2012), soodsate hoia kutega teiste kul tuuride suhtes (Dubiner, 2010), identiteedi kujunemisega (Martin & Stuart-Smith, 1998) ning suurema tundlikkusega kõneleja žestide tõlgenda mises (Yow & Markman, 2011). Psühholoogilisele heaolule kesken duvates uurimustes on leitud, et mõningates kontekstides võib muukeelsete laste psühholoogiline toimetulek olla kohaliku populat siooniga võrreldes parem (Vaage et al, 2009;Vuorenkoski, Kuure, Moilanen, Penninkilampi, & Myhrman, 2000), samuti on leitud, et nendel mitmekeelsetel lastel, kes kõnelevad sihtriigi keelt ladusalt, esineb vähem käitumisprobleeme võrreldes ühekeelsete lastega, sh põhirahvusega, seevastu sihtriigi keelt mitteoskavad nooremas koolieas sisserännanud on emotsionaalsete ja käitumisprobleemide riskirühmas (Wen-Jui & Chien-Chung, 2010).…”
Section: Mitmekeelsus Ja Selle Seosed Sotsiaalse Kohanemisegaunclassified